2022
DOI: 10.3390/genes13061018
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of m6A Writers, Erasers and Readers in Poplar 84K

Abstract: N6-methyladenosine (m6A) RNA modification is a conserved mechanism to regulate gene expression that plays vital roles in the development of plants. However, the m6A RNA modification in forest trees remains limited. Here, we performed a complete analysis of m6A writers, erasers and readers in Poplar 84K, including gene location, gene structures, conserved motifs, phylogenetic relationships, promoter analysis, expression profiles and the homology modeling. We have identified 61 m6A pathway genes in Poplar84K (Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…5 ; Table S 8 ). Similar findings were also found in other plant species such as tea [ 48 ], tomato [ 49 ], and poplar [ 67 ]. The promoter regions of m 6 A regulatory genes in tobacco encompassed a substantial proportion (46%) of light-responsive CREs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…5 ; Table S 8 ). Similar findings were also found in other plant species such as tea [ 48 ], tomato [ 49 ], and poplar [ 67 ]. The promoter regions of m 6 A regulatory genes in tobacco encompassed a substantial proportion (46%) of light-responsive CREs.…”
Section: Discussionsupporting
confidence: 87%
“…For m 6 A writer, the genes from the same branch had similar exon–intron structures and conserved domains, except that NtMTB3 had one more exon than NtMTB4 . Interestingly, NtVIRs had a super long structure with 27 to 28 exons, which was also found in other plants such as tea [ 48 ] and poplar [ 67 ]. MT-A70 domain was found in all tobacco MT families, and NtMTB proteins also contained a MAPK-interacting and spindle-stabilizing protein-like protein domain (MISS).…”
Section: Resultsmentioning
confidence: 76%
“…Hence, it is deserved to further uncover the regulatory mechanism of these m 6 A readers in C. camphora. The cis-regulatory element analysis of C. camphora promoters showed that the promoter regions of the 10 CcYTH genes contain numerous cis-regulatory elements associated with stress responses (Figure 8), which is similar to the findings in various plants such as Arabidopsis, rice, poplar, and so on [23,30,[40][41][42]. The expression levels of genes related to development and stress response are generally high or significantly increased during the developmental stage or under stress treatments.…”
Section: Discussionsupporting
confidence: 79%
“…The phylogenetic tree analysis unveiled the evolutionary patterns of m 6 A writer, eraser, and reader genes as they evolved across a spectrum of plant species, including Rhodophyta (red algae), Chlorophyte (green algae), Tracheophyte (vascular plants), and Angiosperms (comprising eudicots and monocots). In a prior study, a phylogenetic tree was created by comparing the protein sequences of N6-methyladenosine writers, erasers, and readers in Poplar 84K with their counterparts in Arabidopsis and O. sativa to explore their phylogenetic relationships [ 79 ]. In another study on m 6 A genes of Arabidopsis, it was found that methyltransferase domains from various species share close relationships, while other components of methylation are organized differently.…”
Section: Discussionmentioning
confidence: 99%